Cognitive and anti-inflammatory effects of Palmaria palmata in a schizophrenia mouse model: insights into CREB signaling, Iba-1 expression, and CD4+ cell modulation - Yousof, Shimaa Mohammad; Alghamdi, Badrah S.; Alqurashi, Thamer; Alam, Mohammad Zubair; Tash, Reham; El-Fadeal, Noha M. Abd; Abusikkien, Samy A.; Kaddam, Lamis (Frontiers in Neuroscience, 2025)
BackgroundSchizophrenia is a prevalent mental illness characterized by complex behavioral and emotional disturbances, with its underlying molecular mechanisms yet to be fully elucidated.AimThis study aims to examine the neuroprotective effects of Palmaria palmata (Palmaria p.) on cognitive function in a schizophrenia mouse model.MethodsA total of 28 adult male SWR Swiss mice were used over a 30-day period. The animals were randomly divided into four groups (n = 7): control, cuprizone (CPZ) (0.2% CPZ in chow), CPZ + Palmaria p. (600 μg/kg bw/day via gavage), and Palmaria p. alone. The antioxidant activity of Palmaria p. was assessed using a radical scavenging assay. Behavioral assessments, hippocampal (HC) and frontal cortex (FC) gene expression analyses, and histopathological evaluations were conducted.ResultsPalmaria p. demonstrated remarkable antioxidant activity against CPZ-induced oxidative stress. No notable effects were observed in spatial memory, the novel object recognition test (NORT), or anxiety-related behaviors. In the CPZ-treated group, Iba1 and CREB expression levels increased in both the hippocampus (HC) and frontal cortex (FC). In the CPZ + Palmaria p. group, Iba1 expression was reduced by approximately one-fold in the HC and two-fold in the FC, while CREB expression was decreased by approximately two-fold in both regions compared to the CPZ group, indicating attenuation of neuroinflammation and restoration of neuroplasticity. Immunohistochemical analysis revealed a notable decline in CD4+ expression following Palmaria p. administration, suggesting a decrease in the immunological response induced by CPZ.ConclusionThe results highlight the potential of Palmaria p. to enhance neuroplasticity and reduce neuronal inflammation associated with schizophrenia.